Engineering Fluid Mechanics - Song, Hongqing (Springer Singapore, 2018)
This book systematically introduces engineering fluid mechanics in a simple and understandable way, focusing on the basic concepts, principles and methods. Engineering fluid mechanics is necessary for professionals and students in fields such as civil, environmental, mechanical, and petroleum engineering. Unlike most of the current textbooks and monographs, which are too complicated and include huge numbers of math formulas and equations, this book introduces essential concepts and flow rules in a clear and elementary way that can be used in further research. In addition, it provides numerous useful tables and diagrams that can be quickly and directly checked for industry applications. Furthermore, it highlights the connection between free flow and porous flow, which can aid advanced interdisciplinary research such as nanotech and environmental science. Last but not least, each chapter presents a variety of problems to offer readers a better understanding about the principles and applications of fluid mechanics.